Spojrzenie „bez podmiotu” [Recenzja książki Aleksandry Ubertowskiej Historie biotyczne. Pomiędzy estetyką a geotraumą Warszawa: Instytut Badań Literackich PAN, 2020] - Koza, Katarzyna (Zoophilologica. Polish Journal of Animal Studies, 2023)
The text is a review of Aleksandra Ubertowska’s book, Historie biotyczne. Pomiędzy estetyką a geotraumą [Biotic histories. Between aesthetics and geotrauma]. The starting point becomes the biocentric lens applied by the researcher and the geostory behind it. Equally interesting and important are the possibilities of ecocritical theories in interpretation and their application in the Polish ground.